1.x=y+1
x²-2xy+y²+3xy=1,(x-y)²+3xy=1,1+3y(y+1)=1,xy=0
y(y+1)=0,y1=0,y2=-1,x1=1,x2=0
x1=1,y1=0; x2=0,y2=1
2.x+2y=0,x=-2y
x²+y²=6x,4y²+y²=-12y,5y²+12y=0,y(5y+12)=0
y1=0,x1=0 ; y2=-12/5; x2=24/5
3.x²-y²=3,(x+y)(x-y)=3,.(1)
x²-2xy+y²=1,(x-y)²=1,x-y=1,或 x-y=-1
代入(1):x+y=3 或 x+y=-3
x1=2,y1=1 或 x2=-2,y2=-1
4.4x²+4xy+y²=9,(2x+y)²=9,2x+y=3 或 2x+y=-3
x²+5xy-6y²=0,(x-y)(x+6y)=0,x-y=0,或 x+6y=0
(1) x-y=0,x=y
2x+x=3 或 2x+x=-3
x1=1,y1=1 或 x2=-1,y2=-1
(2) x+6y=0,x=-6y
-6y+y=3 或 -6y+y=-3
y=-3/5 或 y=3/5
x3=18/5,y3=-3/5 或 x4=-18/5,y4=3/5
共4个解